Seismic Modeling and Imaging for Complex Structures - A/P Subramaniam, Renuga Devi (Universiti Teknologi PETRONAS, 2016)
Seismic modeling expound the forward process of numerically simulating seismic waves through the earth model to generate seismic data. Forward modeling includes two steps which are velocity model building followed by numerical computation of seismic response. Forward modeling uses either ray tracing or wave equation methods depending on the geological model dimension. In this study, a 2D acoustic wave equation method is used to model the salt dome. As for the accurate positioning of geological events, prestack depth imaging is immensely capable to produce a realistic image of the depth section which consist various geological structures. However, developments to this method are necessary to improve the accuracy of the output depth image in terms of image resolution and positioning. This research focuses on the effect of the parameters of prestack depth imaging on complex structures such as salt domes. We investigate the factors and their sensitivity that affect the accuracy of Kirchhoff depth migration. In the preliminary test, we run a forward modeling of a salt dome model with varying the acquisition geometry and migration aperture distance. Our results show that the consideration of acquisition parameter and migration aperture significantly improves the resolution and quality of the images.